Hubungan Dakwah dan Komunikasi - Muqsi (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2018)
Communication is also a transaction, a symbolic process that allows each individual to relate to one another and manage each other's environment. There are several possibilities that can be done with communication, such as strengthening human relationships, reinforcing attitudes and behaviors of others, as well as changing attitudes and behaviors of others. Da'i convey the message of Islam through symbols to mad'u, and mad'u receive the message, process it and then the response. In the process there is enlightenment by da'i and interpretation of messages by mad'u (object of da'wah). The process of transmission and interpretation would expect its effect to change, attitude and behavior mad'u to a better, more Islami